Holocene fires, forest stability and human occupation in south‐western Amazonia. (27th November 2012) - Urrego, Dunia H.; Bush, Mark B.; Silman, Miles R.; Niccum, Brittany A.; De, Paulina; McMichael, Crystal H.; Hagen, Stephen; Palace, Michael; Vetaas, Ole
Abstract Aim The aim of this study was to assess the effect of Holocene fire activity and drought on the mesic forests of the Upper Beni and the extent of ecotone migration in south‐western Amazonia during the mid‐Holocene. An additional goal was to address the hypothesis of Amazonia as a manufactured landscape prior to the arrival of European colonizers in the New World in ad 1492. Location Lakes Chalalán and Santa Rosa, Upper Beni, Bolivian Amazon. Methods Holocene vegetation and fire activity were reconstructed based on pollen and microcharcoal records from sediments of lakes Chalalán and Santa Rosa. Chronologies were based on accelerator mass spectrometry radiocarbon analyses, and vegetation changes were summarized using detrended correspondence analysis. The normalized difference vegetation index was used to classify and determine the extent of the modern savanna–forest ecotone using MODIS satellite image data. Results Mesic evergreen forests persisted in the Upper Beni throughout the Holocene. Fire was frequent during the early and mid‐Holocene and temporally consistent in both records. Ordination of pollen data showed an increase in forest change during the late Holocene when fire activity was asynchronous in the two records. Main conclusions The Upper Beni sites were not reached by expanding savannas during periods of major environmental change, suggesting forest resilience and a degree of ecotone stability. We associated the largest observed change in these forests with late Holocene fires that were most probably ignited by humans. We found little evidence supporting widespread pre‐1491 cultural landscapes.